Reflection and transmission of circularly polarized light for a layered periodic system with distributed defects - Valeriy V. Yatsyshen (Физика волновых процессов и радиотехнические системы, 2025)
Background. Periodic layered systems form one-dimensional photonic crystals that have many properties of conventional crystals. Of particular interest are the optical properties of such structures, which attract the attention of researchers and engineers due to the prospects for practical applications. Aim. The paper presents the results of calculating the frequency and angular spectra of reflection and transmission of light for a periodic structure with complex embedded defects. Methods. Using the characteristic matrix method, the energy reflection and transmission coefficients are calculated for such a structure using circularly polarized light. The ellipsometric parameters of the reflected and transmitted radiation are analyzed. Results. The paper shows that oblique incidence of light on the studied periodic structure with a defect leads to a wide variety of angular and frequency reflection and transmission spectra, which allows using this structure for selective reflection, as well as for devices that change the nature of the polarization of incident radiation. Conclusion. The use of circularly polarized radiation during its reflection and transmission for periodic media with complex distributed defects allows obtaining new controlled optical devices.